2018
DOI: 10.5371/hp.2018.30.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Intrawound Vancomycin Powder in Primary Total Hip Arthroplasty Increases Rate of Sterile Wound Complications

Abstract: PurposeTotal hip arthroplasty (THA) is a successful surgery for the treatment of hip osteoarthritis; however, the risk of a post-operative prosthetic joint infection (PJI) remains at 1% to 2%. The purpose of this study was to investigate the safety profile of using vancomycin powder (VP) to reduce infection rates by reviewing acute postoperative complications.Materials and MethodsA retrospective review of 265 consecutive patients undergoing THA was performed. The first 128 patients, the control group, did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 28 publications
2
47
0
1
Order By: Relevance
“…Dial et al observed a similar effect in primary hip arthroplasty, with a lowering of the infection rate from 5.5% without vancomycin to 0.7% with intrawound vancomycin powder 13 . However, sterile wound complications were seen in 4.4% of the cases treated with vancomycin, compared with 0% in the control group.…”
Section: Introductionmentioning
confidence: 76%
“…Dial et al observed a similar effect in primary hip arthroplasty, with a lowering of the infection rate from 5.5% without vancomycin to 0.7% with intrawound vancomycin powder 13 . However, sterile wound complications were seen in 4.4% of the cases treated with vancomycin, compared with 0% in the control group.…”
Section: Introductionmentioning
confidence: 76%
“…The recruitment period differed for patients treated with intrawound vancomycin and controls in all but two studies. 27 , 33 Follow-up time was different between the two groups in two studies, 14 , 30 and one study 25 did not report follow-up time. Table II describes patient characteristics including sex, age, BMI, and comorbidities.…”
Section: Resultsmentioning
confidence: 96%
“…27 A total of 4,607 patients were included in our analyses, comprising 2,497 patients treated with intrawound vancomycin and 2,110 controls ( Table II ). All included studies reported the definition of PJI: four 13 , 28 - 30 of them determined the PJI based on the International Consensus Meeting (2013); 31 two, 25 , 26 based on the Musculoskeletal Infection Society (2011) criteria; 32 one, based on treatment method; 33 one, based on articular fluid culture; 27 and one, 14 based on Musculoskeletal Infection Society (2011) criteria and culture. Only one study 30 included patients who underwent UKA (n = 26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dial et al. [16] recently showed a decreased infection rate in a series of primary hip arthroplasties but did find an increased incidence of associated sterile seroma. Results of our investigation demonstrate a significantly decreased overall infection rate (superficial plus PJI) from 2.7% to 0.57% for primary total hip and knee arthroplasty with the addition of intrawound vancomycin.…”
Section: Discussionmentioning
confidence: 95%